Vascularization of kidney organoids: different strategies and perspectives - Raykhel, Irina; Nishikawa, Masaki; Sakai, Yasuyuki; Vainio, Seppo J.; Skovorodkin, Ilya (Frontiers in Urology, 2024)
Kidney diseases such as glomerulopathy and nephron dysfunction are estimated to grow to more than 900 million cases by 2030, in 45% of which kidney transplantation will be required, representing a major challenge for biomedicine. A wealth of progress has been made to model human diseases using induced pluripotent stem cells (iPSCs) in vitro differentiated to a variety of organoids, including kidney organoids, and in developing various microfluidics-based organ-on-a-chip (OoC) systems based on them. With the combination of targeted gene editing capacities, relevant polymorphic genetic variants can be established in such organoid models to advance evidence-based medicine. However, the major drawback of the current organoid disease models is the lack of functional endothelial vasculature, which especially concerns the kidney, the function of which is strongly associated with blood flow. The design of novel medical devices using tissue engineering approaches such as kidney organoids is also strongly dependent on the understanding of the fundamental principles of nephrogenesis and the vascularization of organs and tissues. Developmental vascularization of the kidney has been an area of intense research for decades. However, there is still no consensus among researchers on how exactly the vascularization of the kidney occurs in normal and pathological conditions. This lack of consensus is partly due to the lack of an appropriate model system to study renal vascularization during nephrogenesis. In this review, we will describe recent progress in the areas of kidney vasculature development, kidney organoids in general and assembled on microfluidic devices in particular. We will focus on the in vitro vasculature of kidney organoids in microfluidic OoC model systems to study kidney diseases and on the perspectives of tissue engineering for the modeling of kidney diseases and the design of bioartificial medical devices. We also aim to summarize the information related to the key mechanisms of intercellular communication during nephrogenesis and the formation of the renal vasculature in an OoC setup.